2016
DOI: 10.3998/ark.5550190.p009.590
|View full text |Cite
|
Sign up to set email alerts
|

Copper-catalyzed cyanation of aryl halides with sodium nitroprusside in polyethylene glycol 400 (PEG-400)

Abstract: A simple and efficient CuI/PEG-400 catalytic protocol for the cyanation of aryl halides employing sodium nitroprusside, Na 2 [Fe(CN) 5 NO]·2H 2 O, as a new cyanation reagent was developed. The present cyanation reagent shows higher activity and gave the desired products in yields of up to 96%. In the present protocol, a variety of aryl bromides and iodides were cyanated smoothly with a wide range of substrate scope.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…In a similar study, Wang and co-workers showed that ethylenediamine in conjunction with Cu­(OAc) 2 .H 2 O could promote the cyanation of aryl bromides and activated aryl chlorides with K 4 [Fe­(CN) 6 ] in the presence of catalytic quantities of KI and Na 2 CO 3 . In addition, Chen and co-workers demonstrated Na 2 [Fe­(CN) 5 NO]·2H 2 O was a better reagent than K 4 [Fe­(CN) 6 ] for the cyanation of aryl iodides/bromides in PEG-400 solvent . In the presence of Na 2 [Fe­(CN) 5 NO]·2H 2 O, NaOH, and a catalytic amount of CuI (10 mol %), aryl iodides were converted into corresponding nitriles in good yields.…”
Section: Cyanationmentioning
confidence: 94%
“…In a similar study, Wang and co-workers showed that ethylenediamine in conjunction with Cu­(OAc) 2 .H 2 O could promote the cyanation of aryl bromides and activated aryl chlorides with K 4 [Fe­(CN) 6 ] in the presence of catalytic quantities of KI and Na 2 CO 3 . In addition, Chen and co-workers demonstrated Na 2 [Fe­(CN) 5 NO]·2H 2 O was a better reagent than K 4 [Fe­(CN) 6 ] for the cyanation of aryl iodides/bromides in PEG-400 solvent . In the presence of Na 2 [Fe­(CN) 5 NO]·2H 2 O, NaOH, and a catalytic amount of CuI (10 mol %), aryl iodides were converted into corresponding nitriles in good yields.…”
Section: Cyanationmentioning
confidence: 94%
“…In this scenario, transition-metal catalyzed syntheses of aryl cyanides from aryl halides were explored and were found to be highly acceptable. Among them palladium, [12][13][14][15] nickel [16][17][18] and copper [19][20][21] catalyzed cyanation have been well explored. Takagi et al in 1973 introduced the rst palladium-catalyzed cyanation from bromo and iodoarenes using potassium cyanide.…”
Section: Introductionmentioning
confidence: 99%
“…[b] Yields refer to the isolated pure products and the structures of the products were confirmed by 1 H NMR and 13 C NMR spectral data [6f,8a–c,f] (Refer to ESI).…”
Section: Resultsmentioning
confidence: 99%
“…[a] Reaction conditions: arylhalide (1 mmol), K 4 [Fe(CN) 6 ] (0.2 mmol), DMED/TBAB (4 mL) and Fe 3 O 4 @SiO 2 @PrNCu (0.2 mol%) at 80 °C. [b] Yields refer to the isolated pure products and the structures of the products were confirmed by 1 H NMR and 13 C NMR spectral data [6f,8a–c,f] (Refer to ESI). [c] Reaction was carried out using 0.5 mol% of Fe 3 O 4 @SiO 2 @PrNCu catalyst.…”
Section: Resultsmentioning
confidence: 99%